AN ANALYSIS OF STUDENTS’ ABILITY IN BASIC ENGLISH VOCABULARY OF THE SEVENTH GRADE AT SMPN 3 BENGKALIS - Kolijah, Kolijah; Silvana, Ade; Fadli, Noval (Ensiklopedia Research and Community Service Review, 2025)
This study aims to determine students’ ability in basic English vocabulary and to determine the factors that hinder students’ ability in basic English vocabulary of the seventh grade at SMPN 3 Bengkalis. This study used a descriptive research with mixed methods approach. The samples were 45 students from 90 students in class VII. The researcher chose the sample with a random sampling technique. The researcher used a multiple-choice test instrument to determine students’ ability, and then used an interview instrument to determine the factors that hinder students’ ability in class VII. The results of the test data obtained from 45 students showed a total score of 1955. With these results the researcher has obtained an average score of all students 43.44 so that the level of students’ basic vocabulary ability is classified as fair, where this level students’ basic English vocabulary ability is not stated as high or low but rather moderate. Meanwhile, interview data shows that the students feel dizzy when their teacher explains English vocabulary, which is caused by their lack of understanding of the word and their struggle to understand english language learning. As a result, they experience physical symptoms like dizziness during the lesson. Additionally, the researcher found that the students in grade VII at SMPN 3 Bengkalis lack motivation to learn English vocabulary. Keywords : descriptive qualitative; basic; ability; English vocabulary